Structural plasticity in mesencephalic dopaminergic neurons produced by drugs of abuse: critical role of BDNF and dopamine - Collo, Ginetta; Cavalleri, Laura; Spano, PierFranco (Frontiers in Pharmacology, 2014)
Mesencephalic dopaminergic neurons were suggested to be a critical physiopathology substrate for addiction disorders. Among neuroadaptive processes to addictive drugs, structural plasticity has attracted attention. While structural plasticity occurs at both pre- and post-synaptic levels in the mesolimbic dopaminergic system, the present review focuses only on dopaminergic neurons. Exposures to addictive drugs determine two opposite structural responses, hypothrophic plasticity produced by opioids and cannabinoids (in particular during the early withdrawal phase) and hypertrophic plasticity, mostly driven by psychostimulants and nicotine. In vitro and in vivo studies indentified BDNF and extracellular dopamine as two critical factors in determining structural plasticity, the two molecules sharing similar intracellular pathways involved in cell soma and dendrite growth, the MEK-ERK1/2 and the PI3K-Akt-mTOR, via preferential activation of TrkB and dopamine D3 receptors, respectively. At present information regarding specific structural changes associated to the various stages of the addiction cycle is incomplete. Encouraging neuroimaging data in humans indirectly support the preclinical evidence of hypotrophic and hypertrophic effects, suggesting a possible differential engagement of dopamine neurons in parallel and partially converging circuits controlling motivation, stress and emotions.